2012
DOI: 10.1166/jnn.2012.6438
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite of Cu–TiO2–SiO2 with High Photoactive Performance for Degradation of Rhodamine B Dye in Aqueous Wastewater

Abstract: The nanocomposite of Cu-TiO2-SiO2 photocatalyst have been prepared by a sol-gel method, which is used for the degradation of Rhodamine B (RB) as a probe that is notorious organic compound present in dyes wastewater. Morphological and structural characteristics of the Cu-TiO2-SiO2 nanocomposite were studied with low temperature N2 adsorption (BET), X-ray diffraction (XRD), scanning electron microscopy (SEM) and UV-vis diffuse reflectance spectroscopy (DRS). The Fourier transformed infrared spectroscopy (FT-IR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Under UV/Vis irradiation, the electrons in the valence band (VB) of TiO 2 are promoted to Cu II species in the Cu x O clusters, which results in the transformation of Cu II into Cu I and the holes remain in the valence band . Li et al . showed that Cu‐modified TiO 2 ‐SiO 2 nanocomposites (Cu/Ti=0.01:1) prepared by a sol–gel method and calcined at 500 °C for 3 h exhibited a higher photocatalytic activity than commercial TiO 2 (Degussa P25) for the degradation of Rhodamine B dye under both UV and visible‐light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Under UV/Vis irradiation, the electrons in the valence band (VB) of TiO 2 are promoted to Cu II species in the Cu x O clusters, which results in the transformation of Cu II into Cu I and the holes remain in the valence band . Li et al . showed that Cu‐modified TiO 2 ‐SiO 2 nanocomposites (Cu/Ti=0.01:1) prepared by a sol–gel method and calcined at 500 °C for 3 h exhibited a higher photocatalytic activity than commercial TiO 2 (Degussa P25) for the degradation of Rhodamine B dye under both UV and visible‐light irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the dopant Si enhanced the water absorption and the more OH were formed. Thereby, the photo-catalytic activity of AC -SiO 2 was increased [17]. The XRD results show broad peak at 2θ = 48.0, 54.0 and 62.0 corresponding to the (200), ( 211) and (204) crystal planes reflection of anatase.…”
Section: Characterization Of the Photocatalystmentioning
confidence: 92%
“…Theoretical simulations [37] indicate that Cu is the most stable when highly dispersed at anatase (101) surface and in a 2+ oxidation state. Electronic interactions facilitated via the mechanism of charge transfer (metal-to-metal charge transfer; Cu-O-Ti connections) increase the lifetime of surface holes and increase the photocatalytic activity through charge carrier separation [38].…”
Section: Introductionmentioning
confidence: 99%